The Wet'suwet'en Aboriginal Title: A Case for Breach of Fiduciary Duty - Auger, Christine (Université d'Ottawa / University of Ottawa, 2022)
At the author’s request, the abstract has been removed due to the confidential nature of the thesis. It will be added once the embargo period has passed.
Keywords: Fiduciary duties; Wet'suwet'en Aboriginal Title; Coastal GasLink pipeline; Hereditary leadership; Honour of the Crown; Constitutional Crown duties